The sphinx of the Charles : a year at Harvard with Harry Parker - Ayer, Toby (Guilford, Connecticut : Lyons Press, 2016)
Harry Parker was probably the most important figure in American rowing of the past century. His heavyweight crews at Harvard topped the leagues more consistently than any other team (they won the Eastern Sprints regatta, against most of the top college crews, more than three times as often as their nearest rival). From the time they miraculously won the 1963 Harvard-Yale Race at the end of his first year at the helm, his varsity didn't lose a race for six years, and they didn't lose to Yale until the Reagan administration. He was the first US National Team coach, and oversaw five Olympic teams.
Foreword; Introduction: Harry Parker and the Cauldron of Pain; Chapter 1-September: Another Great Year; Chapter 2-October: Mother Newell; Chapter 3-November: Steady at the Catch; Chapter 4-December-January: Tour de Stade; Chapter 5-February: Keep Digging; Chapter 6-March: On This One; Chapter 7-April: Whaddaya Say; Chapter 8-May: Great Day!; Chapter 9-June: Well Rowed Harvard, Well Rowed Yale (Or, "You're Gonna Love Red Top!"); Afterword: The Royal Regatta; Acknowledgments; Notes; A Rowing Glossary; Index; About the Author.
Includes bibliographical references.
Description based on print version record and CIP data provided by publisher.
eBooks on EBSCOhost
Keywords: Parker, Harold Lambert, -- 1935-2013.; Ayer, Toby; Harvard University -- Rowing -- History; Ayer, Toby; Parker, Harold Lambert, -- 1935-2013; Harvard University; Rowing coaches -- Massachusetts -- Biography; Aviron -- Entraîneurs -- Massachusetts -- Biographies; SPORTS & RECREATION -- Water Sports; Rowing; Rowing coaches; Massachusetts; Biographies; History